1996
DOI: 10.1111/j.1365-3156.1996.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mouth‐to‐mask ventilation in resuscitation of asphyxic newborn babies. A pilot study

Abstract: The aim of the study was to compare the effectiveness of mouth-to-mask ventilation (MM) in neonatal asphyxia with bag-and-mask ventilation (BM). A new mouth-to-mask infant resuscitation system was constructed. The study was performed in two university clinics with different resources. The KEM Hospital in Bombay was well equipped and neonatologists took part in all resuscitations; Muhimbili Medical Centre in Dar es Salaam was understaffed and had no physicians available at resuscitation. Therefore, different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Massawe et al [192] found that mouth-to-mask and bag-to-mask ventilation were comparable in terms of Apgar scores, heart rate and time to first breath. The only RCT on preterm newborns [189] evaluated the impact of nasal CPAP on BPD and the need for intubation, reporting a lower number of intubations in neonates given nasal CPAP on admission to the NICU compared to those who were not given nCPAP.…”
Section: Resultsmentioning
confidence: 99%
“…Massawe et al [192] found that mouth-to-mask and bag-to-mask ventilation were comparable in terms of Apgar scores, heart rate and time to first breath. The only RCT on preterm newborns [189] evaluated the impact of nasal CPAP on BPD and the need for intubation, reporting a lower number of intubations in neonates given nasal CPAP on admission to the NICU compared to those who were not given nCPAP.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of technical concerns were noted regarding proper use of resuscitation equipment by CHWs or TBAs, but virtually all respondents considered drying and stimulating the baby and clearing the mouth appropriate tasks, despite the WHO recommendation against clearing the mouth [29]. The virtually unanimous indictment of the mouth-to-tube device, which cannot be used at more than 20 breaths per minute [30], compared to the recommended 40–60 breaths per minute, suggests that use of this technology should be reviewed. Regarding care of the baby with complications of birth asphyxia, most respondents believed referral, keeping the baby dry and warm, and feeding expressed breastmilk were appropriate, emphasizing referral.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining a patent airway and providing effective positive pressure ventilation (PPV), which is currently achieved in the delivery room by means of a face mask (FM) or a tracheal tube (TT), is standard treatment and forms the cornerstone of emergency neonatal care in First World countries [2], but making these interventions feasible in settings where resources are limited is particularly challenging [4,5]. Since its introduction into clinical practice, the LMA has gained increasing popularity for resuscitation of adult as well as pediatric patients, and more recently in neonatal resuscitation.…”
Section: Introductionmentioning
confidence: 99%